2016
DOI: 10.1200/jco.2016.67.4788
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival With Prostate Radiation in Addition to Androgen Deprivation Therapy for Men With Newly Diagnosed Metastatic Prostate Cancer

Abstract: In this large contemporary analysis, men with mPCa receiving prostate RT and ADT lived substantially longer than men treated with ADT alone. Prospective trials evaluating local therapies for mPCa are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
135
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(147 citation statements)
references
References 33 publications
3
135
1
3
Order By: Relevance
“…Although exact definitions of oligometastatic are variable, it conceptually represents an intermediate step between localized disease and widespread metastases . It is hypothesized that these patients with oligometastatic disease may benefit from local therapy . It is further hypothesized that eradication of all sites of oligometastatic disease could result in clinical benefits .…”
Section: Areas For Further Researchmentioning
confidence: 99%
“…Although exact definitions of oligometastatic are variable, it conceptually represents an intermediate step between localized disease and widespread metastases . It is hypothesized that these patients with oligometastatic disease may benefit from local therapy . It is further hypothesized that eradication of all sites of oligometastatic disease could result in clinical benefits .…”
Section: Areas For Further Researchmentioning
confidence: 99%
“…23 Men with N1 disease treated with RP have a reduced risk of death from prostate cancer compared to those treated with non-curative therapies. 24,25 A reduction in prostate cancer-specific mortality in men with M1 disease whose primary tumor is treated definitively has also been shown in population-based studies, 2628 and the feasibility of RP in this population has been established. 29,30 Prospective trials to test this question are combining surgery or radiation with “best systemic therapy” (NCT01751438) or radiation to the primary tumor with systemic therapy (NCT00268476, NCT01957436, and NTR271).…”
Section: Discussionmentioning
confidence: 87%
“…11 The authors showed an overall survival benefit through the addition of RT to ADT for these patients on both univariable and multivariable analysis (HR 0.62, 95% CI 0.55-0.71, P < 0.001) adjusted for age, year, race, comorbidity score, bPSA level, Gleason score, T stage, N stage, chemotherapy administration, treating facility and insurance status. 11 Subgroup analyses from that study showed a greater benefit with prostate RT among patients with Gleason scores ≤8 and T1-3 (vs T4) tumors. 11 Subgroup analyses from that study showed a greater benefit with prostate RT among patients with Gleason scores ≤8 and T1-3 (vs T4) tumors.…”
Section: Studies Reporting Oncological Outcomesmentioning
confidence: 92%